The relationship of stress on the eating behavior among secondary school teachers in Selangor / Maizatul Farhana Jaafar @ Mat Zin - Jaafar @ Mat Zin, Maizatul Farhana (2016)
Nowadays, one of factor that can contribute to stress in daily life occur due to occupational for example working as a teachers. Stress occur among individual itself in order to accomplish own satisfaction level and also occurs due environmental working condition that become more adventures. When individual experience on high stress level, this can effect on the hormone production and continuously lead to alterations of eating behavior. Thus, eating behavior continuously can effect on the nutritional status of the individual. This research was conducted generally to identify the relationship of stress on eating behavior among secondary school teachers in Selangor. This cross sectional study included on secondary school teachers in SMK Puncak Alam, SMK Puncak Alam 3 and SMK Saujana Utama. The total subjects participated in this research were 105 secondary school teachers aged between 25 to 58 years old that selected by using convenience sampling method. The data clearly stated that majority of the secondary school teachers' represents higher value of BM! level, waist hip ratio, body fat percentage and blood pressure when comparing to the normal range. Stress level among secondary school teachers in Selangor showed that majority of the teachers had normal level of stress based on the score from the DASS-42 presented depression score (90.5%), anxiety score (66.7%) and stress score (86.7%). Meanwhile for TFEQ-RI8, the data stated that most of the subject had low cognitive restraint (88.6%) and emotional eating was 55.2%. However, the data differ for uncontrolled scores as subjects tend to have moderate level score (63.8%). In addition, it also indicated that only uncontrolled eating shows significant value for depression, anxiety and stress for negative correlation. The nutritional status for the teachers need to be taking into consideration and some strategies must be planned in ordered to improve on the nutritional status. As the level of depression increase, this will contribute to increase severity of uncontrolled eating. With that, this factor should be considered during the development of strategies to improve on overall nutritional status of secondary school teachers.